Respuesta :

3 + (+7) + (-4) = 6

[tex]\text{Hey there!}[/tex]

[tex]\text{If -h = -7 then replace -h with -7}[/tex]

[tex]\text{3 + (-7) + (-4)}\rightarrow\text{ which is converted to: 3 - 7 - 4}[/tex]

[tex]\text{3 - 7 - 4}\\\text{3 - 7 = -4}\\\text{-4 - 4 = answer}\\\text{- ,  + = - ; negative \& positive =  negative}\\\\\boxed{\mathsf{We\ know\ our\ answer\ will\ now\  be\ a\ negative}}\\\text{-4 - 4 = -8}\\\\\boxed{\boxed{\bf{Answer: -8}}}\checkmark[/tex]

[tex]\text{Good luck on your assignment and enjoy your day!}[/tex]

~[tex]\frak{LoveYourselfFirst:)}[/tex]